Asymptotic behavior of solutions for Klein-Gordon and thermoelastic plate systems - Silva, Cládio Odair Pereira da (2019)
In this work we study a Klein-Gordon system with mixed boundary conditions and a thermoelastic plate system with Neumann boundary conditions. In the first system we analyze the existence and uniqueness of global solution. Moreover, we show the exponential decay of energy associated to solution. In the second system we show the existence, uniform boundedness, and continuity of the global attractors when some reaction terms are concentrated in a neighborhood of the boundary and this neighborhood shrinks to boundary as a parameter goes to zero.